Escalation of Tauhid Education in Families to Address Teenage Promiscuity - Waqiah, Sitti Qamariatul; Arifin, Syamsul (Asatiza: Jurnal Pendidikan, 2024)
Promiscuity is abnormal or deviant behavior that threatens the future of the nation's children. Many factors influence promiscuous behavior, including weak religious values, a disharmonious family environment, very low self-control, minimal awareness of the dangers of promiscuity, and unhealthy lifestyles. The family, as the first school for teenage children, plays a very vital role in preventing promiscuity by instilling the values of tauhid in the family environment. Tauhid education is often considered as spiritual intelligence and a fundamental character trait for every Muslim. With the protection provided by strong tauhid education, it becomes a shield or weapon against the dangers of promiscuity. This research is a qualitative design, involving the review of books, scientific works, popular works, and other literature related to the theme studied. The research addresses the concept of tauhid education and how it is instilled in families to deal with promiscuity. The findings indicate that the concept of tauhid education comprises three interrelated criteria (mutualistic symbiosis) that cannot be separated: Tauhid Rububiyah, Tauhid Uluhiyah, and Tauhid al-Hakimiyyah. The methods used to instill tauhid education in the family include five approaches: tauhid, example, habituation, advice, and supervision.